THE ANALYSIS OF HUVAIDO'S GHAZAL “KUYUB ISHQ O’TIDA, EY DO’STLAR, BAG’RI KABOB O‘TTUM” (Modern education and development, 2025)
Khojanazar Huvaido is a mature representative of the Kokan literary environment and a master poet. His lyrical legacy was published as a devan. In this article, the poet's ghazal, which begins with the words “Kuyub ishq o‘tida, ey do‘stlar, bag‘ri kabab o‘ttum” is analyzed. In it, the creator's ideological direction, artistic skills, and the uniqueness of the image of divine love are analyzed. In the analysis of ghazals, the art of tashbeh, tajnis, exaggeration, exclamation, tazad is used skillfully.